2019
DOI: 10.1002/path.5321
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin‐2 contributes to tumor progression in preclinical models of small intestinal neuroendocrine tumors

Abstract: The identification of novel regulators of tumor progression is a key challenge to gain knowledge on the biology of small intestinal neuroendocrine tumors (SI‐NETs). We recently identified the loss of the axon guidance protein semaphorin 3F as a protumoral event in SI‐NETs. Interestingly the expression of its receptor neuropilin‐2 (NRP‐2) was still maintained. This study aimed at deciphering the potential role of NRP‐2 as a contributor to SI‐NET progression. The role of NRP‐2 in SI‐NET progression was addressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…NRP2 is primarily expressed in the nervous and vascular systems and is important for the development of embryos by enhancing VEGF-VEGFR binding [ 6 ]. Recent studies have reported that the neuropilin family is involved in tumor metastasis and is correlated with poor prognosis [ 7 , 8 ]. Moreover, NRP2 has been found to be highly expressed in pancreatic islet cells and endocrine pancreatic tumors [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…NRP2 is primarily expressed in the nervous and vascular systems and is important for the development of embryos by enhancing VEGF-VEGFR binding [ 6 ]. Recent studies have reported that the neuropilin family is involved in tumor metastasis and is correlated with poor prognosis [ 7 , 8 ]. Moreover, NRP2 has been found to be highly expressed in pancreatic islet cells and endocrine pancreatic tumors [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In-depth analysis in preclinical mouse models of SI-NET suggested that knockdown of NRP2 imparted antitumor effects by VEGFR2 downregulation. NRP-2 inhibition led to decreased tumor cell viability and higher susceptibility towards therapeutic agents [110].…”
Section: Gastric Cancermentioning
confidence: 99%
“…Semaphorins have shown both pro-and anti-angiogenic effects in NETs, and their activity is the result of the interaction with neuropilin and plexin receptors (7). Neuropilin receptors have been found in both pancreatic, intestinal and pulmonary NETs (39)(40)(41), while data on the expression of plexin receptors in NETs Schematic overview of the main pathways regulating angiogenesis in NETs. By acting on endothelial cells, VEGF stimulates both vascular endothelial mitogenesis and permeability.…”
Section: Angiogenesis In Netsmentioning
confidence: 99%
“…Semaphorins have shown both pro- and anti-angiogenic effects in NETs, and their activity is the result of the interaction with neuropilin and plexin receptors ( 7 ). Neuropilin receptors have been found in both pancreatic, intestinal and pulmonary NETs ( 39 41 ), while data on the expression of plexin receptors in NETs are currently lacking. Experiments in RIP1-Tag2 mice have shown that the expression of semaphorin 3A (SEMA3A) is progressively lost during tumor progression and that the inhibition of SEMA3A during the angiogenic switch may enhance tumor formation.…”
Section: Angiogenesis In Netsmentioning
confidence: 99%